(untitled) (Journal of Universal Science Research, 2024)
In this article, discussing the importance of evaluation in determining student‘ reading proficiency in higher education is the paper‘s primary objective. Assisting teachers in determining evaluation criteria and providing students with feedback on their progress in reading comprehension is another objective. The article also describes how assessment methods and evaluation standards are used to different reading comprehension skill levels. The research paper‘s final objective is to show teachers and students the advantages of formative assessment.